Dampak Sosial Pemanfaatan Tanah Ulayat untuk Perkebunan Inti Rakyat bagi Masyarakat Kenagarian - Destuliadi Destuliadi; Sudirman Sudirman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study is to determine the impact that occurs in the utilization of customary land for people's nucleus plantations. This research method is descriptive research with a qualitative approach. The results of the first study show that the use of communal land in the development of PT. Perkebunan Nusantara VI causes changes related to location, customs, facilities, family, socio-economic conditions, socio-cultural conditions, and religion. Second, in the deliberations, the ninik mamak and the nagari government reached a consensus on the consequences of the use of ulayat land by PT. Nusantara Plantation VI. Nagari Gunung Malintang Community. Ninik mamak received cash assistance of Rp. 2,500/ha and assistance of 6,500 main oil palm seeds for 46 ha of plantation land. The conclusions of this study indicate that the impact of development has a significant effect on the order of indigenous peoples, including facilities, socio-economic conditions, and socio-culture. Keywords: Impact, Social and Indigenous Land